Arabic Syntactic Structures - A Linguistic Study According To The Neo-khalilian Theory - Fatiha Khelout (Al-Lisaniyyat)
The neo-Khalilian theory ( Hadj Salah : 1979, 2011) is a contemporary linguistic theory based on the nahw al' Arabi (النحو العربي) of early grammarians of Arabic. This paper presents a linguistic analysis of the syntactic structures in Arabic using what is known in the neo-Khalilian theory as the tectonie. This latter is made up of governing units (R), governed units (T1) and peripheral units (D)